Gingival Enlargement in Orthodontic Patients: Effect of Treatment Duration - Haider Zahid, Nofil Ahmad, Mir Hadi Faisal, Waqas Sabir, Sofia Shehzad, Naseer Hasan (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the effect of the duration of ﬁxed orthodontic treatment on gingival enlargement (GE) in patients. Study Design: A cross-sectional study Place and Duration: Department of Orthodontics in Frontier Medical and Dental College from June 2021 – December 2021. Methodology: A total of 260 patients aged 10-30 years were enrolled. All the patients were divided into 4 groups: G0, G1, G2 and G3. A predesigned questionnaire was used to collect data. Clinical examinations were performed by an examiner. Results: There was a total of 260 patients with 107 male and 153 female participants. Increasing means of plaque, gingivitis, and GE in G0, G1, and G2 were found. No signiﬁcant differences were observed between G2 and G3. Conclusion: With increasing the duration of orthodontic treatment, the incidence of GE also increased. Keywords: Gingival enlargement, fixed orthodontic treatment